PENGARUH ABRASI AIR LAUT TERHADAP KUAT TEKAN DAN MODULUS ELASTISITAS BETON MUTU TINGGI DENGAN BAHAN TAMBAH ABU SEKAM PADI - Nabhan Nabhan; Kusno Adi Sambowo; Endang Rismunarsi (Program Studi Teknik Sipil FT UNS, 2014)
As a maritime nation , the use of concrete in Indonesia can not be separated from sea barrier bulidings or breakwater buildings. New methods areheld to develope the type of construction materials, both in the construction of the pier ( pier , jetties ) , beacon or bridge as a liaison between islands. Aggressive environment is an area which is dangerous for the durability of concrete . Abrasion , in this case to be one of the important factors thatshould be studied in concrete durability problems . One of the types of construction materials development is the building block of rice husk ash.Theuse of rice husk ash for additive materials is one of the added material innovations that can improve the adhesion between the particles so that theconcrete into a dense concrete .This study aims to cylindrical specimen of 80 mm diameter and 150 mm high by 40 pieces , for testing the elasticmodulus of concrete using the same cylindrical specimen with a compressive strength test and taken 40 % of the compressive strength of 40 pieces .Variations used are high strength concrete with rice husk ash material added to the percentage of 0 % , 13 % , 15 % , 16 % , 17 % , and 20%.On the analisys of the XRF testing rice husk ash , which obtained the largest content of SiO2 is equal to 82.59 % , which shows that the silicacontent of the rice husk ash there is enormous . And it can improve the quality of concrete compressive strength . The test results showed that theuse of rice husk ash with added levels of 17 % by weight of cement gives a strong increase in the quality press and the optimum value of modulus ofelasticity in aggressive environments . Reaction of calcium chloride ( CaCl2 ) contained in sea water causes the concrete compressive strength increasedmore rapidly than normal water treatment at the same age .